Exploring the benefits and challenges of health professionals' participation in online health communities: Emergence of (dis)empowerment processes and outcomes. (February 2017) - Atanasova, Sara; Kamin, Tanja; Petrič, Gregor
Highlights: Participation in OHCs brings benefits also to health professionals, not only users. Health professional moderators see themselves as agents of users' empowerment process/outcomes. Being a health professional moderator can be personally and professionally (dis)empowering. Participation in OHCs can improve the quality of professional-patient interaction. Abstract: Background: Various online applications and service has led to the development of online health communities (OHCs), which in addition to the peer-to-peer communication offer patients and other users also interaction with health professionals. While the benefits and challenges of patients and other users' participation in OHCs have been extensively studied, a thorough examination of how health professionals as moderators (i.e., those who provide clinical expertise to patients and other users in OHCs) experience participation in OHCs is lacking. Objective: The aim of this study is to explore the main benefits and challenges of health professional moderators' participation in the OHCs. Methods: The study undertakes an exploratory qualitative study, with in-depth semi-structured interviews with health professional moderators ( n = 7) participating in the largest OHC in Slovenia, Med.Over.Net . The data was analysed using inductive thematic analysis approach and principles of grounded theory. Results: Four themes of health professional moderators' experiences were identified: (a) benefits of addressing OHC users' health-related needs, (b) challenges of addressing OHC users' health-related needs, (c) health professional moderators' benefits, and (d) health professional moderators' challenges. Conclusions: This small study demonstrates that health professional participating in OHCs as moderators perceive themselves as facilitators of patients and other OHC's users empowering processes and outcomes, in which OHC's users improve their health literacy, develop skills, expand their social support, and gain other important resources necessary when dealing with health-related issues. Health professional moderator's role, however, also involves several duties, responsibilities and limitations that are often experienced as difficulties in providing patients and other users with adequate counselling and online medical service. OHCs also represent an important terrain for personal and professional empowerment of health professional moderators, although the presence of disempowering processes also needs to be noted.